Identification of robust microsatellite markers for wild pig fecal DNA. Issue 6 (10th June 2016) - Kierepka, Elizabeth M.; Unger, Shem D.; Keiter, David A.; Beasley, James C.; Rhodes, Olin E.; Cunningham, Fred L.; Piaggio, Antoinette J.
ABSTRACT: Collection of fecal samples for use in a genetic capture‐mark‐recapture framework has become popular as a noninvasive method of monitoring wildlife populations. A major caveat to this process, however, is that fecal samples often yield low quality DNA that is prone to genotyping errors, potentially leading to biases in population parameter estimation. Therefore, considerable care is required to identify robust genetic markers, especially in hot or humid conditions that may accelerate DNA degradation. We identified microsatellite loci in wild pig ( Sus scrofa ) fecal samples that were robust and informative within warm, humid ecosystems. To examine how degradation affected genotyping success, we sampled pig feces across 5 days and calculated how the number of quantitative polymerase chain reaction (qPCR) cycles required to reach the fluorescent threshold ( C t ) changed over time. We identified 17 microsatellite loci that had high polymorphism and amplification success and low genotyping error rates (0–0.050 per locus). In the degradation experiment, C t increased over the 5 days, but in the absence of rain, the majority of samples produced accurate genotypes after 5 days (2, 211/2, 550 genotypes). Based on the high amplification success and low error rates, even after 5 days of exposure to warm, humid conditions, these loci are useful for estimating population parameters in pig fecal samples. © 2016 The Wildlife Society.